Leadership Results - Salicru, Sebastian (Ascent Audio, 2019)
Leadership Results explores the fall of traditional leadership thinking and the struggling multibillion dollar leadership development industry that is failing to deliver results, and explains the mindset, skills, ways of being, and methods that will get results in the new context and evolving paradigm. The Leadership Results model is practical and predictive, providing a way forward for companies seeking to build sustainable leadership capacity, develop individual leaders, boost employee engagement, and deliver breakthrough results through shared and collective leadership. Actionable steps guide you through the process of evolving leadership culture to see increased productivity, growth opportunities, and ensured profitability borne on a culture of trust, collaboration, fairness, and a commitment to innovation and real prosperity. Leaders, coaches, trainers, OD practitioners, change agents, and students will find insightful guidance, thought-provoking discussion, and illustrative case studies that will help them: rethink leadership to make a stronger impact, take bold action to change the status quo, marry strategic and innovation leadership into a force for real change, and stop making the same mistakes and start forging a new path forward.